The Motivational and Academic Consequences of Elementary Mathematics Environments: Do Constructivist Innovations and Reforms Make a Difference? - Hickey, Daniel T.; Moore, Allison L.; Pellegrino, James W. (American educational research journal, 2001)
This study examined the effects of a videodisc-based mathematical problem-solving series known as The Adventures of Jasper Woodbury, as implemented by one school district within a constructivist-inspired reform of its math curricula. The motivational and academic consequences of both the specific innovation and the broader reforms were examined in 19 fifth-grade classrooms in two pairs of closely matched schools. One pair of schools served higher-achieving high-socioeconomic status (SES) students while the other pair served relatively lower-achieving low-SES students. Significantly larger gains on the Mathematical Problem-solving subtest of the ITBS were documented in the 10 classrooms where the Jasper activities were implemented, and in the 10 classrooms that were ranked as relatively more consistent with the broader curricular reform goals. The largest relative gains were found in the five classrooms that both used the Jasper activities and were ranked more consistent with the broader reforms. The positive consequences of both the Jasper activities and the broader reforms were documented in both pairs of schools. The implications of these results are discussed relative to current proposals for curricular reform and research on educational innovations.